Microeconomics : a very short introduction - "Dixit, Avinash K" (Oxford, 2014)
The issues of microeconomics - including individuals' financial choices and firms' decisions about hiring and firing - have a large impact on the economic world, arguably as much, if not more than, macroeconomics. In this book, Avinash Dixit clearly explains what microeconomics is by using examples from around the world.
Keywords: Economics